Unraveling Job Crafting in the Workplace in the Last Decade: a Systematic Literature Review - Retno Kurniasih; Ade Irma Anggraeni; Ratno Purnomo (Cita konsultindo, 2024)
This study aims to analyze the complex evolution of job crafting research, exploring the elements that influence and are influenced by it, the theories that have been employed, and the general advancement of the idea in the past decade. This review is grounded in 28 published articles from the Scopus database. The selection process was rigorous, choosing papers that have garnered significant citations and were published between 2014 and 2024. A template based on the PRISMA statement to outline the comprehensive process of selecting relevant articles. The study makes two significant contributions. The authors conduct an extensive literature review to provide a thorough overview of the concept of Job Crafting as it has evolved in the past decade. The authors present a comprehensive analysis of the Job Crafting literature, meticulously examining the frequency of annual publications. These organizations predominantly adopt Job Crafting practices, the journals that publish pertinent articles, the diverse disciplines contributing to Job Crafting-related publications, and the geographical locations where most Job Crafting studies have occurred. The author's emphasize the need for tools, models, and methods to support organizations implementing job crafting, especially in developing countries.